PENGARUH KARAKTERISTIK INDIVIDU, BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI MTS AL JAMIYATUL WASHLIYAH TEMBUNG - Dedy Dhamhudi; Fauzan Azim (Juripol (Jurnal Institusi Politeknik Ganesha Medan), 2021)
This research was conducted in Mts Al Jamiyatul Wasliyah temdude, which has a purpose: 1) to know and analyze the influence of individual characteristics on employee performance 2) to know and analyze the impact of workload on performance Employees. 3) to know and analyse the impact of the work environment on employee performance. 4) to know and analyze the influence of individual characteristics, workloads and work environment to employees ' performance. The data collection techniques in this study used interviews and questionnaires to include administrative officers and teachers at Mts Aljamiyatul Washliyah, amounting to 60 people. In this study used multiple linear regression analyses, coefficient of determination test, F test and T test. The results of this study indicate there is a tangible influence of individual characteristic variables, workload, working environment to variable performance personnel at Mts Al Jamiyatul Washliyah temdude.